2021
DOI: 10.1097/md.0000000000026595
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transplantation on neutrophil extracellular trap formation in patients with end-stage renal disease

Abstract: Increased neutrophil extracellular trap (NET) formation associates with high cardiovascular risk and mortality in patients with end-stage renal disease (ESRD). However, the effect of transplantation on NETs and its associated markers remains unclear. This study aimed to characterize circulating citrullinated Histone H3 (H3cit) and Peptidyl Arginase Deiminase 4 (PAD4) in ESRD patients undergoing transplantation and evaluate the ability of their neutrophils to release NETs. This prospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…However, the release of NETs can also cause tissue damage, and excessive or inappropriate NETs formation has been implicated in the development of autoimmune and in ammatory diseases. It is possible that NETs could be formed in response to the stress of surgery or because of in ammation or infection during the transplantation process [38][39][40][41][42][43][44]. More research is needed to understand the role of NETs in organ transplantation and the potential consequences of NET formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the release of NETs can also cause tissue damage, and excessive or inappropriate NETs formation has been implicated in the development of autoimmune and in ammatory diseases. It is possible that NETs could be formed in response to the stress of surgery or because of in ammation or infection during the transplantation process [38][39][40][41][42][43][44]. More research is needed to understand the role of NETs in organ transplantation and the potential consequences of NET formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the release of NETs can also cause tissue damage, and excessive or inappropriate NET formation has been implicated in the development of autoimmune and inflammatory diseases. It is possible that NETs could be formed in response to the stress of surgery or because of inflammation or infection during the transplantation process [40][41][42][43][44][45][46]. More research is needed to understand the role of NETs in organ transplantation and the potential consequences of NET formation.…”
Section: Discussionmentioning
confidence: 99%
“…There are contrasting findings on the stimuli-induced NETs formation capacity of neutrophils in CKD stage 5 (Table 2). Some authors observed increased NETs production by neutrophils isolated from dialysis patients upon phorbol-12-myristate-13-acetate (PMA) stimulation, 148,149 along with increased PAD4 levels in serum 149 or increased NE activity in both resting and PMA-stimulated neutrophils. 148 In contrast, others reported a decreased NETs formation capacity of isolated neutrophils from dialysis patients upon stimulation with PMA, lipopolysaccharide, or the Ca 2+ ionophore A23187 compared with healthy controls 15 (Table 2).…”
Section: Neutrophils and Nets As Contributors To Thrombotic Risk In Ckd?mentioning
confidence: 99%
“…differences between predialysis patients or patients on hemodialysis or peritoneal dialysis. 149 Also, increased levels of histone-DNA complexes 147,148,150 as well as myeloperoxidase-DNA complexes 150 have been detected in hemodialysis patients, with even higher levels in those reaching a composite endpoint of all-cause mortality or loss of vascular access, compared to those who did not 150 (Table 1).…”
Section: Compendium On Increased Risk Of Cardiovascular Complications...mentioning
confidence: 99%
See 1 more Smart Citation